Bon Jovi : when we were beautiful - Bon Jovi, Jon; Griffin, Phil (Collins Design, 2009)
Timed to coincide with the band's twenty-fifth anniversary, an inside portrait of Bon Jovi follows them on their 2008 Lost Highway tour, explores the history of the band, and discusses the band members' lives both at home and on the road.